Customer experience management rebooted : are you an experience brand or an efficiency brand? - Walden, Steven (Palgrave Macmillan, 2017)
Customer experience management is not about managing every objective "experience" your customers have with you. It's about understanding, measuring and creating "experiences" that customers "value". So while service and efficiency are wonderful things, they represent "business as usual"; the ticket to the game, the platform from which "experiences" are created not the experience itself! The message of this book is that businesses are at risk! Their uber focus on efficiency is leading them to miss the chance to connect more closely with their customer base and deliver on the creative potential of their brand. They ignore the fact that technology is an enabler of the "experience" it is not "the experience". Customers are not data -- they are people: living, breathing, contradictory, infuriating bundles of cognitive and emotionally-driven responses to stimuli. "Experience" deals with how customers think, feel and behave -- the things that motivate them to act which go beyond frequently forgettable efficiency. This means differentiating by providing new and better experiences based on a deeper understanding of what motivates customers to buy. To do that we must leave the objective, quantitative, world of quality management and enter the subjective, qualitative, world of customer's psychology. Walden reboots our understanding of customer experience, showing us what it means, how to measure it, what we need to do to manage it and how we can gain financially from it. Understand, measure, create and do -- but first of all, understand.
Keywords: Customer relations -- Management.; Consumer satisfaction.; Customer services.; elektronické knihy; electronic books